Use of Vibrational Spectroscopy to Study Protein and DNA Structure, Hydration, and Binding of Biomolecules: A Combined Theoretical and Experimental Approach - Jalkanen, Karl; Juergensen, V.; Claussen, A.; Rahim, A.; Jensen, G.; Wade, R.; Nardi, F.; Jung, C.; Degtyarenko, I.; Nieminen, R.; Herrmann, F.; Knapp-Mohammady, M; et al. (John Wiley & Sons, 2006)
No abstract.